2006
DOI: 10.1021/bi0601048
|View full text |Cite
|
Sign up to set email alerts
|

High Yield of M-Side Electron Transfer in Mutants of Rhodobacter capsulatus Reaction Centers Lacking the L-Side Bacteriopheophytin

Abstract: We present studies on a series of photosynthetic reaction center (RC) mutants created in the background of the Rhodobacter capsulatus D(LL) mutant, in which the D helix of the M subunit has been substituted with that from the L subunit. Previous work on the D(LL) mutant in chromatophore preparations showed that RCs assembled without the bacteriopheophytin H(L) electron acceptor and performed no charge separation following light absorption. We have successfully isolated poly-His-tagged D(LL) RCs by using the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(97 citation statements)
references
References 28 publications
(37 reference statements)
5
91
1
Order By: Relevance
“…Wild-type, D LL , and D LL -FY L F M RCs were expressed, isolated, and purified using the detergent Deriphat 160-C as described previously. 89 For measurements of D LL RCs in LDAO, the detergent was exchanged to LDAO after initial Deriphat 160-C purification. Due to extremely low yields, D LL -FY L F M was not subjected to buffer exchange and so was not examined in LDAO.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wild-type, D LL , and D LL -FY L F M RCs were expressed, isolated, and purified using the detergent Deriphat 160-C as described previously. 89 For measurements of D LL RCs in LDAO, the detergent was exchanged to LDAO after initial Deriphat 160-C purification. Due to extremely low yields, D LL -FY L F M was not subjected to buffer exchange and so was not examined in LDAO.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…We previously showed that for D LL -FY L F M in Deriphat at 295 K, P* decay is well described by a single exponential (∼55 ps time constant) and gives a 70% yield of P + H M -and a 30% yield of deactivation to the ground state. 89 These values give a rate constant for electron transfer from P* to P + H M -of 0.7/(55 ps) ) (78 ps)…”
Section: Heterogeneous-rc Model For D Llmentioning
confidence: 99%
“…Although significant yields of P ϩ H B Ϫ formation have been reported in some R. capsulatus mutants (17,31,32,35,38), the largest rate constant for P* 3 P ϩ H B Ϫ is ϳ(40 ps)…”
Section: Discussionmentioning
confidence: 99%
“…Further characterization of primary electron transfer events in select mutant RCs utilized a transient absorption apparatus having 130-fs excitation and white light probe flashes operating at 10 Hz (described previously in Refs. 31,38). RCs were held at ϳ10°C in an ice-cooled reservoir and flowed through a 2-mm pathlength cell.…”
Section: Growth-r Capsulatus Strains Were Cultured Onmentioning
confidence: 99%
See 1 more Smart Citation